Making stationary of splinedistribution with help of scale factors method - Нечипорук, В. В. (Proceedings of National Aviation University (archive), 2021)
Making stationary of splinedistribution is considered, whih describe pice-nonstationary processes of faults by calculations of reliability tests with help of scale factors method.